Lake Water Levels and Associated Hydrologic Characteristics in the Conterminous U.S. (8th January 2020) - Fergus, C. Emi; Brooks, J. Renée; Kaufmann, Philip R.; Herlihy, Alan T.; Pollard, Amina I.; Weber, Marc H.; Paulsen, Steven G.
Abstract: Establishing baseline hydrologic characteristics for lakes in the United States (U.S.) is critical to evaluate changes to lake hydrology. We used the U.S. Environmental Protection Agency National Lakes Assessment 2007 and 2012 surveys to assess hydrologic characteristics of a population of 45, 000 lakes in the conterminous U.S. based on probability samples of 1, 000 lakes/yr distributed across nine ecoregions. Lake hydrologic study variables include water‐level drawdown (i.e., vertical decline and horizontal littoral exposure) and two water stable isotope‐derived parameters: evaporation‐to‐inflow (E:I) and water residence time. We present (1) national and regional distributions of the study variables for both natural and man‐made lakes and (2) differences in these characteristics between 2007 and 2012. In 2007, 59% of the population of U.S. lakes had Greater than normal or Excessive drawdown relative to water levels in ecoregional reference lakes with minimal human disturbances; whereas in 2012, only 20% of lakes were significantly drawn down beyond normal ranges. Water isotope‐derived variables did not differ significantly between survey years in contrast to drawdown. Median E:I was 20% indicating that flow‐through processes dominated lake water regimes. For 75% of U.S. lakes, water residence time was less than one year and was longer in natural vs. man‐made lakes. Our study provides baseline ranges to assess local and regional lake hydrologic status and inform management decisions in changing environmental conditions. Abstract : Research Impact Statement : Probability survey of U.S. lakes showed water‐level decline is common but variable across years (60%–20%). Lake water residence times were < 1 year for most lakes and less variable across years.